The level of hs-CRP in coronary artery ectasia and its response to statin and angiotensin-converting enzyme inhibitor treatment - Ozbay, Yilmaz; Akbulut, Mehmet; Balin, Mehmet; Kayancicek, Hidayet; Baydas, Adil; Korkmaz, Hasan (Hindawi Ltd, 2007)
Background/Aim. Coronary artery ectasia (CAE) was thought of as a variant of atherosclerosis. C-reactive protein (CRP) which is among the most sensitive markers of systemic inflammation, and elevation of systemic and local levels of this inflammatory marker which has been associated with an increased risk for cardiovascular disease in the obstructive coronary artery disease (O-CAD) are well known, but little was known in CAE. The anti-inflammatory effects of statins and the effect of angiotensin-converting enzyme (ACE) inhibitors on endothelial dysfunction are well established in atherosclerosis. The aim of the present study was to investigate CRP level and its response to statin and ACE inhibitor treatment in CAE. Materials and method. We measured serum hs-CRP level in 40 CAE (26 males, mean age: 56.32 +/- 9 years) and 41 O-CAD (34 males, mean age: 57.19 +/- 10 years) patients referred for elective coronary angiography at baseline and after 3-month statin and ACE inhibitor treatment. Results. Plasma hs-CRP levels were significantly higher in CAE group than O-CAD group at baseline (2.68 +/- 66 mg/L versus 1, 64 +/- 64, resp., P < .0001). Plasma hs-CRP levels significantly decreased from baseline 3 months later in the CE (from 2.68 +/- 0.66 mg/L to 1.2 +/- 0.53 mg/L, P < .0001) as well as in the O-CAD group (from 1.64 +/- 0.64 mg/L to 1.01 +/- 0.56 mg/L, P < .001). Conclusion. We think that hs-CRP measurement may be a good prognostic value in CAE patients as in stenotic ones. Further placebo-controlled studies are needed to evaluate the clinical significance of this decrease in hs-CRP. Copyright (c) 2007 Yilmaz Ozbay et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: C-Reactive Protein; Acute-Phase Proteins; Disease; Homocysteine; Inflammation; Predictors